Serratia proteamaculans mediated alteration of tomato defense system and growth parameters in response to early blight pathogen Alternaria solani infection. (August 2018) - Youssef, Sahar A.; Tartoura, Kamel A.; Greash, Alaa G.
Abstract: Early blight caused by Alternaria solani is a devastating tomato plant disease affecting one of the most economically important vegetable crops worldwide. The plant growth promoting rhizobacteria are known to suppress plant pathogens and induce systemic resistance response in infected plants. The objectives of this study were to evaluate the efficacy of Serratia proteamaculans to induce the defense machinery and enhance tomato seedlings growth. Primary in vitro examination revealed a constant suppression of fungal growth. Under greenhouse conditions, bacterial suspensions at rate 50 ml/plant (10 8  cfu/ml) were incorporated once into pots containing tomato seedlings challenged or not with fungal spores. Results showed that S. proteamaculans was able to alleviate disease symptoms; severity reached 48.75% compared to control. Furthermore, the strain enhanced significantly tomato growth and chlorophyll content. In addition, bacterial treatment enhanced activity of plant defense enzymes and pathogenesis related proteins including guaiacol peroxidase (GPX), superoxide dismutase (SOD), phenylalanine ammonia-lyase (PAL) and β-1, 3 glucanase reached 2, 7, 3, 2 folds at days 5, 7, 6, 5 respectively. The obtained results suggested that application of S. proteamaculans as soil drench efficiently controlled tomato early blight disease and enhanced plant growth. Highlights: S. proteamaculans was examined against early blight pathogen A. solani in vitro. S. proteamaculans increased tomato growth parameters and chlorophyll content. Application of biocontrol agent induced tomato defense machinery and pathogenesis related protein.